1982
DOI: 10.1136/bmj.285.6349.1177
|View full text |Cite
|
Sign up to set email alerts
|

Promoting children's home safety.

Abstract: Home accidents are the main cause of death and morbidity in early childhood. Working-class children are at greatest risk. A study in an inner city area of the effects of a national television campaign about child accident prevention and of a locally designed health education initiative showed that 55% of families with young children in the study area did not watch any of the television programmes. Only 9% of a group specially encouraged to watch the programmes took any action to make their homes safer. In a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…This included six RCTs (Baudier et al, 1988;Clamp & Kendrick, 1998;Colver, Hutchinson, & Judson, 1982;Gielen et al, 2007;Paul, Sanson-Fisher, & Redman, 1994;Watson et al, 2005) and one CBA (Schwarz, Grisso, Miles, Holmes, & Sutton, 1993), evaluating interventions providing safety education (OR 1.61, 95% CI 1.10À2.36 (Gielen et al, 2007)) and safety education plus equipment, with effect sizes ranging from RR 1.15 95% CI 1.03À1.28 (Clamp & Kendrick, 1998) to OR 14.30 95% CI 4.22À18.46 (Colver et al, 1982. The remaining 18 studies (see Table 4) evaluating a range of interventions including safety education, tailored safety education, safety education plus equipment found no significant difference in safe storage of medicines between treatment groups.…”
Section: Interventions Promoting Safe Storage Of Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…This included six RCTs (Baudier et al, 1988;Clamp & Kendrick, 1998;Colver, Hutchinson, & Judson, 1982;Gielen et al, 2007;Paul, Sanson-Fisher, & Redman, 1994;Watson et al, 2005) and one CBA (Schwarz, Grisso, Miles, Holmes, & Sutton, 1993), evaluating interventions providing safety education (OR 1.61, 95% CI 1.10À2.36 (Gielen et al, 2007)) and safety education plus equipment, with effect sizes ranging from RR 1.15 95% CI 1.03À1.28 (Clamp & Kendrick, 1998) to OR 14.30 95% CI 4.22À18.46 (Colver et al, 1982. The remaining 18 studies (see Table 4) evaluating a range of interventions including safety education, tailored safety education, safety education plus equipment found no significant difference in safe storage of medicines between treatment groups.…”
Section: Interventions Promoting Safe Storage Of Medicinesmentioning
confidence: 99%
“…Of the 31 primary studies, six reported significantly more intervention group families stored household and other products safely. Four RCTs (Colver et al, 1982;Hendrickson, 2002;Paul et al, 1994;Watson et al, 2005) provided safety education plus equipment and home safety inspections with effect sizes ranging from OR 1.31 95% CI 1.07À1.60 (Watson et al, 2005) to OR 15.79, 95% CI 4.65À53.62 (Hendrickson, 2005). One RCT provided safety education plus equipment (OR 2.21 95% CI 1.40À3.51 (Woolf et al, 1992)) and one RCT gave home safety counselling and safety equipment with specific injury focussed instructions in the ED prior to discharge (OR 2.58 95% CI 1.12À5.94) (Posner, Hawkins, GarciaEspana, & Durbin, 2004).…”
Section: Interventions Promoting Safe Storage Of Medicinesmentioning
confidence: 99%
“…The largest proportion of respondents (46%) instead endorsed, 'Most injuries can be prevented.' In another investigation from the UK, when mothers were asked, 'Do you think that children's accidents are mostly just bad luck or mostly could be prevented,' 89% of respondents replied, 'Mostly could be prevented' (Colver et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…These conclusions suggested a limited role for the media, although the review does identify a number of interventions which had a successful media component (e.g. McAvoy & Raza,1991, Colver, Hutchinson & Judson, 1982.…”
Section: Media Interventions and Disadvantaged Groupsmentioning
confidence: 96%